Establishing the physiological, anthropometric and training characteristics, and pacing patterns of runners racing in a tropical ultra-marathon - Tan, Loong Seng Philip (Department of Human Biology, 2024)
Background: The popularity of ultra-marathons has rapidly increased in recent years, especially in Southeast Asia, with more recreational runners entering the field. The physiological, anthropometric, and training characteristics of runners participating in these ultra-marathons run in high temperature and humidity, along with their pacing have not been documented. Knowing these parameters and their relationship with performance in this group of participants are important for prescribing appropriate training to maximise performance and minimise the risk of injury, especially heat injury, as well as choosing the optimal pacing strategy for races. Aim: The first aim of the thesis was to compare and determine the differences in the physiological, anthropometric, and training characteristics of the finishers (FIN) and nonfinishers (N-FIN) in a tropical ultra-marathon. The second aim was to establish and compare the pacing patterns of fast and slow FIN in the same race. Two studies were conducted to achieve these aims. Methods: For the first study, two groups of participants of the 161-km category of the race (FIN; N=12 and N-FIN; N=14) completed a series of anthropometric and physiological measurements over two separate sessions at least three weeks prior to the race. Training sessions starting from six weeks prior to the race were recorded. Sum of 7 skinfolds, arm and calf girths, VO2max and peak treadmill speed (PTS) were taken during session 1 while the lactate threshold (LT) and running economy (RE) were assessed during session 2. For the second study, FIN of the 161-km (N=47) and 101-km (N=120) categories of the race were divided into thirds (Group A-C) by merit of finishing time. Altogether, 17 and 11 split times were recorded for the 161-km and 101-km finishers, respectively, and used to calculate the mean running speed for each distance segment. Running speed for the first segment was normalised to 100, with all subsequent splits adjusted accordingly. Running speed during the last 5 km was calculated against the mean race pace to establish the existence of an “end spurt”. Main findings: For the first study, effect size (ES) calculations showed moderate and clear differences in the lactate concentration at LT1 (ES = 0.88; P = 0.05), velocity at LT2 (ES = 0.70; P = 0.07), longest run attempted (ES = 0.73; P = 0.07) and number of cross-training hours (ES = 0.73; P = 0.06) between the FIN and N-FIN. For the second study, a reverse J-shaped pacing profile was demonstrated in all groups for both distance categories. Only 38% of the finishers executed an end spurt. In the 101-km category, in comparison to group B and C, group A maintained a significantly more even pace (P = 0.013 and 0.001, respectively) and completed the race at a significantly higher percent of initial starting speed (P = 0.001 and 0.001, respectively). Descriptive data also revealed that the top five finishers displayed a “herdbehaviour” by staying close to the lead runner in the initial portion of the race. Conclusion: Findings from the studies conducted suggest that from a physiological perspective, the ability to finish a 161-km ultra-marathon in a hot and humid climate might be differentiated by metabolic attributes via LT measurements. For training, runners should not neglect the importance of the long runs and should incorporate cross-training to provide additional stimuli to the body while allowing the running muscles to recover from. Finally, to avoid a significant decline in running speed during the later parts of the race, recreational ultrarunners should adopt a conservative sustainable starting speed. Less competitive runners should set realistic performance goals while competitive runners with a specific time goal should consider running in packs of similar pace.